2017
DOI: 10.1177/1971400917714280
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging in the assessment of choroid plexus aging

Abstract: Recent studies have pointed out dysfunction and histopathological changes of the choroid plexuses (CPs) with aging. This paper reviews apparent diffusion coefficient (ADC) values of the CPs for age-related changes. All the brain MR images of the patients between January 2013 and June 2014 in our Radiology Department were retrospectively investigated. Patients with major cranial abnormalities (brain tumors, hyperacute or acute ischemia, developmental anomalies, hemorrhage, hydrocephaly) were excluded. Diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Due to the multifunctional role of the CP, it is difficult to discern the dominant source and purpose of volume enlargement during normative aging, which necessitates further investigations. Our finding of higher MD values with age is consistent with Alicioglu et al (2017). This age-related increase in MD is further supported by our findings that FA significantly decreased with age and that T 1 and T 2 significantly increased with age.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Due to the multifunctional role of the CP, it is difficult to discern the dominant source and purpose of volume enlargement during normative aging, which necessitates further investigations. Our finding of higher MD values with age is consistent with Alicioglu et al (2017). This age-related increase in MD is further supported by our findings that FA significantly decreased with age and that T 1 and T 2 significantly increased with age.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our MD measure exhibited significant differences between men and women, with men exhibiting higher MD values. Alicioglu et al (2017) observed that women experience a steeper increase in MD after the age of 61 as compared to men. Further, several studies have shown that women exhibit higher CBF as compared to men (Devous et al, 1986;Rodriguez et al, 1988;Podreka et al, 1989;Gur and Gur, 1990;Esposito et al, 1996;Parkes et al, 2004;Liu et al, 2012Liu et al, , 2016Alisch et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…DTI metrics have been measured in the ChPs of human subjects thus showing the feasibility of this imaging technique to characterize the ChPs despite their small size (Grech-Sollars et al, 2015). The apparent diffusion coefficient (ADC), reflecting the molecular motion of water in the interstitial space, was shown to increase with aging in ChPs (Alicioglu et al, 2017). According to the authors, this effect may be related to increased water diffusion across the epithelium via paracellular spaces, thus signaling BCSFB malfunction.…”
Section: Resultsmentioning
confidence: 99%
“…The intuitive postulate that cell loss and atrophy results in the ability of water molecules to diffuse more freely and with less directional hindrance in WM can explain these findings. These relationships extend into other specific regions of the brain 182,186–191 and the cervical spinal cord 192 . Although some initial studies indicated that there was no left‐right asymmetry in the fractional anisotropy, later work suggested that some asymmetry may arise during aging 193 …”
Section: Mr Parameter Changes With Agementioning
confidence: 94%